The use of carbon adsorbents for the removal of perfluoroalkyl acids from potable reuse systems. (October 2017) - Inyang, Mandu; Dickenson, Eric R.V.
Abstract: Bench- and pilot-scale sorption tests were used to probe the performance of several biochars at removing perfluoroalkyl acids (PFAA) from field waters, compared to granular activated carbon (GAC). Screening tests using organic matter-free water resulted in hardwood (HWC) ( K d = 41 L g −1 ) and pinewood (PWC) ( K d = 49 L g −1 ) biochars having the highest perfluorooctanoic acid (PFOA) removal performance that was comparable to bituminous coal GAC ( K d = 41 L g −1 ). PWC and HWC had a stronger affinity for PFOA sorbed in Lake Mead surface water (KF = 11 mg (1−n) L n g −1 ) containing a lower (2 mg L −1 ) dissolved organic carbon (DOC) concentration than in a tertiary-filtered wastewater (KF = 8 mg (1−n) L n g −1 ) with DOC of 4.9 mg L −1 . A pilot-scale study was performed using three parallel adsorbers (GAC, anthracite, and HWC biochar) treating the same tertiary-filtered wastewater. Compared to HWC, and anthracite, GAC was the most effective in mitigating perfluoropentanoic acid (PFPnA), perfluorohexanoic acid (PHxA), PFOA, perfluorooctane sulfonic acid (PFOS), and DOC (45–67% removed at 4354 bed volumes) followed by HWC, and then anthracite. Based on bench- and pilot-scale results, shorter-chain PFAA [perfluorobutanoic acid (PFBA), PFPnA, or PFHxA] were more difficult to remove with both biochar and GAC than the longer-chain, PFOS and PFOA. Highlights: PFAA adsorption by biochar and GAC was investigated using bench and pilot tests. Biochar affinity to PFOA was higher in surface water than in treated wastewater. Pilot adsorbers most effective towards PFOA and PFOS removal were: GAC > biochar. Biochar and GAC were less effective towards shorter-chain PFAA.